Techno-economic study and optimal sizing of a stand-alone photovoltaic water pumping system - Muhsen D.H.; Ghazali A.B.; Khatib T.; Abdulabbas T.E. (John Wiley and Sons Ltd, 2023)
Costs; Digital storage; Electric load loss; Iterative methods; Life cycle; Meteorology; Numerical methods; Photovoltaic cells; Probability; Pumping plants; Pumps; Solar energy; Solar power generation; Life cycle costs (LCC); Meteorological data; Photovoltaic; Photovoltaic pumping system; Photovoltaic water pumping; Sizing; Techno-economic studies; Water pumping systems; Loss of load probability